Reducing risk of weed infestation and labor burden of weed management in cropping systems - Kayeke, M.J.; Nhamo, N.; Chikoye, David (Elsevier, 2017)
Weeds are a major biological yield reducing factor in most cropping systems in Africa. The annual cost of weed control has been estimated to be $4.3 billion in Africa. This figure is expected to increase as a result of climate change effects on weed species and ecological conditions for a range of weeds. Similarly, the labor burden that weeding imposes on farm families is expected to increase. Although a range of weed management practices have evolved over the past five decades, farmers still face a mammoth task in meeting the demands of applying these technologies. Cultural, mechanical, chemical, and biological weed management technologies exist; however, their utilization by smallholder farmers still leaves large gaps in terms of efficiency, timeliness, and effectiveness. For instance, large amount of time is still employed in mechanical methods against the prevailing situation, where labor availability is limited during critical peak periods. Although tillage methods have developed parallel to other technologies their contribution to the weed seed bank dynamics and manipulation need to be reviewed in light of developing efficient weed control methods. The overall weed ecology in the region has changed character in response to management, rainfall, carbon dioxide, and temperature patterns in southern Africa suggesting the need to revisit the control methods in place and designing new ones to tackle future scenarios.